EFFECTIVENESS OF AUDIO VISUAL MEDIA FOR DENTAL CAVITIES IN ENHANCING CHILDREN'S KNOWLEDGE - Harto, Toto; Berta Afriani; Suci Adelia (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Dental health rates, especially cavities in children, are high, this is because awareness is still low in maintaining dental health. Low awareness is influenced by low knowledge in maintaining dental health which can have an impact on behavior, especially primary school-age children. Good knowledge is an important foundation in shaping healthy behavior. Health promotion efforts are an effective strategy in increasing children's knowledge. The purpose of the study was to determine the effectiveness of audio-visual media for cavities in increasing children's knowledge at State Elementary School 43 OKU. Quantitative method using pre-experimental One Group pre-test and post-test design was used in this study. Wilcoxon test was used to analyze the data. This study involved 146 respondents, who were selected using purposive sampling method. The study used a questionnaire to collect data on knowledge. The results showed that there was an increase in value after the intervention was given greater than the previous value, obtained P-value = 0.000 from the statistical test results, meaning that there was an effect of health education using audio visual media for cavities in increasing children's knowledge.